Novel Instruments for the Implementation of Electrochemotherapy Protocols: From Bench Side to Veterinary Clinic. Issue 3 (27th October 2016) - Spugnini, Enrico P.; Fais, Stefano; Azzarito, Tommaso; Baldi, Alfonso
Abstract : Electrochemotherapy (ECT) is a medical strategy that allows an increased efficacy of chemotherapy agents after the application of permeabilizing electric pulses having appropriate characteristics (form, voltage, frequency). In the past 10 years, the clinical efficacy of this therapeutic approach in several spontaneous models of tumors in animals has been shown. Moreover, some of the molecular and cellular mechanisms responsible for this phenomenon have been elucidated. Our group has been deeply involved in the development of new ECT protocols for companion animals, implementing the use of the technique as first line treatment, and evaluating different chemotherapy agents in laboratory animals as well as pets. This article summarizes the most important advances in veterinary ECT, including the development of novel equipment, therapeutic protocols, and their translation to humans. J. Cell. Physiol. 232: 490–495, 2017. © 2016 Wiley Periodicals, Inc. Abstract : Electrochemotherapy (ECT) is a medical strategy that allows an increased efficacy of chemotherapy agents after the application of permeabilizing electric pulses having appropriate characteristics (form, voltage, frequency). Our group has been deeply involved in the development of new ECT protocols for companion animals, implementing the use of the technique as first line treatment, and evaluating different chemotherapy agents in laboratory animals as well as pets. This article summarizes the most important advances in veterinary ECT, including the development of novel equipment, therapeutic protocols, and their translation to humans.